Investigating Animal Remains in Estonia - Lõugas, Lembi; Rannamäe, Eve (Archaeologia Lituana, 2020)
In Estonia, faunal remains have been an important part of archaeological material since the 19th century. During the 20th century, the interest in faunal history was rather volatile, but gained some stability during the 1990s. Since then, zooarchaeology in Estonia has developed substantially, focusing on a variety of topics. Together with methods from traditional zooarchaeology, interdisciplinary methods like the studies of ancient DNA and stable isotopes are increasingly used. However, despite the growing understanding of the importance of faunal remains in archaeological and historical research, there are still problems with collecting animal remains during the fieldwork and documenting and organising them. On the other hand, interest in scientific methods and destructive sampling of the osseous remains have become increasingly popular in science projects and international collaboration. In order to use osteological collections reasonably and ethically, proper systemisation is essential.In Estonia, there are two research centres for zooarchaeology, where scientific collections are administered – Tallinn University and the University of Tartu. Tallinn collections comprise material mostly from the northern part of the country, plus an extensive reference collection for fish has been developed there. In Tartu, mostly material from southern Estonia is managed, together with continuously expanding reference collection of mammals and birds. To improve the gathering and management of the osteological material in Estonia and reduce the shortage for storage space, a new central repository for osteological collections (both human and animal) was established in 2019. Concurrently, a new central database for the osteological data was created.In this paper, we introduce the zooarchaeological collections and some of the latest research topics in Estonia with an aim to broaden the understanding and potential of zooarchaeology in the Baltic region.
Keywords: zooarchaeology; research collections; reference collections; Estonia